Cleaner technologies to combat heavy metal toxicity - Rebello, Sharrel; Sivaprasad, M. S.; Anoopkumar, A. N.; Jayakrishnan, Lekshmi; Aneesh, Embalil Mathachan; Narisetty, Vivek; Sindhu, Raveendran; Binod, Parameswaran; Pugazhendhi, Arivalagan; Pandey, Ashok (Elsevier, 2021)
Heavy metals frequently occur as silent poisons present in our daily diet, the environment we live and the products we use, leaving us victims to various associated drastic health and ecological bad effects even in meagre quantities. The prevalence of heavy metals can be traced from children's toys, electronic goods, industrial effluents, pesticide preparation, and even in drinking water in some instances; necessitating methods to remediate them. The current review discusses the various physicochemical and biological methods employed to tackle the problem of heavy metal pollution. Apart from the conventional methods following the principles of adsorption, precipitation, coagulation, and various separation techniques, the advancements made in the directions of biological heavy metal detoxification using microbes, plants, algae have been critically analyzed to identify the specific utility of different agents for specific heavy metal removal. The review paper is a nutshell of different heavy metal remediation strategies, their merits, demerits, and modifications done to alleviate process of heavy metal pollution.
Keywords: Heavy metal; Biosorption; Ultrafiltration; Nanoremediation; Phytoremediation; Microbe